Interorganizational Project Urgency, Problems, and Solutions: A Systematic Literature Review - Laura, Laura; Raharjo, Teguh (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
Interorganizational projects involve two or more organizations to work jointly on a shared activity for a finite time. By doing interorganizational projects, organizations can be more competitive in increasingly varied and volatile markets. The benefits of interorganizational projects are followed by a difficult challenge that is to align difference between members of the project, so the benefits remain poor. A systematic literature review is performed to know what problems and solutions of an interorganizational projects are. This research also provided information about the urgency of an interorganizational project to balance the problem.